Adaptability: literature and cinema redux. Issue 2 (3rd May 2016) - Jeannelle, Jean-Louis
Abstract: This article opposes the notions of adaptation and adaptability, the latter understood here as a complex commercial, screenwriting and critical process. Following the sociological methods endorsed by Simone Murray in The Adaptation Industry, the author studies the concrete aspects of this process of evaluation, development and use of the adaptability of literary works through an examination of the case of a French company: Best Seller to Box Office, a company created to identify the 'adaptability quotient' of contemporary fiction and non-fiction works. The composition of adaptation spec sheets, with the purpose of measuring and highlighting adaptability potential, makes up one of the essential elements of this business, which is relatively new to France. This article examines the particular nature of the business, especially the interface between different facets of the adaptation process.